2015
DOI: 10.1016/j.hlc.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Duration with the Morbidity and Mortality of Coronary Artery Disease: A Meta-analysis of Prospective Studies

Abstract: Short sleep duration was associated with higher morbidity of CAD, and short sleepers and long sleepers had higher risk for CAD mortality. Keeping normal sleep duration is an appropriate recommendation to prevent and control CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 39 publications
1
22
1
Order By: Relevance
“…Previous studies indicated that the associations varied when stratified by gender [55,56] and fatal cases [23], but no differences were detected in association with either short or long sleep duration and CHD in our meta-analysis. Besides, we found a completely inverse result in European for long sleep duration with two studies, which needed to be confirmed further with more studies.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Previous studies indicated that the associations varied when stratified by gender [55,56] and fatal cases [23], but no differences were detected in association with either short or long sleep duration and CHD in our meta-analysis. Besides, we found a completely inverse result in European for long sleep duration with two studies, which needed to be confirmed further with more studies.…”
Section: Discussioncontrasting
confidence: 79%
“…Several possible reasons are contributed to it, for example, the categories of sleep duration differed across studies [46,47]. A meta-analysis in 2011 showed both short and long sleep duration were associated with an increased risk of CHD [18], but another one in 2015 just found association between long sleep duration and mortality of CHD, not between long sleep duration and morbidity of CHD [23]. However, they did not use a dose-response method to analyze the relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most extensively studied sleep component is sleep duration (8). Systematic reviews identified shorter and/or longer sleep duration as associated with a wide variety of clinical outcomes, including obesity (9), metabolic syndrome (10), diabetes (11), hypertension (12), cardiovascular disease (13), stroke (14), and mortality (15). Regarding CKD, a few cohort studies identified shorter sleep duration to be associated with proteinuria (16) and GFR decline (17,18) in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have linked markers of circadian disruption (e.g., shift work, extreme/disturbed sleeping patterns, weaker circadian activity rhythms) with adverse health outcomes, including obesity[2, 3], type 2 diabetes[4, 5], cardiovascular disease[68], dementia[9], and mortality[1013]. Because circadian disturbances have been implicated in accelerated aging[14], they have implications for overall health and function in older adults.…”
Section: Introductionmentioning
confidence: 99%